Antibiotic-Prescribed Infections in Patients Receiving Home Care Services - Aykanat Yurtsever, Burcu; Yurtsever, Ceyhun; Atasoy, Volkan; Hacısalihoğlu, Ayşenur (Baiman Bauntung Batuah Center, 2023)
In our study, it was aimed to examine